2017
DOI: 10.3390/su10010033
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Influencing Business Model Innovation for Sustainable Buildings

Abstract: Despite significant policy drives, the wide adoption of sustainable building (SB) is hindered by factors such as high upfront cost and long payback period. Business model (BM) innovation is therefore highly demanded to help SB professionals to cope with the challenges and convert the value of SB into profit. Nevertheless, few studies examined BM innovation in the building sector and factors influencing BM innovation for SB are unclear. This paper aims to identify the critical factors that propel companies to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Some authors explored BMI for sustainability (Baumgartner & Rauter, 2017; Franca, Broman, Robert, Basile, & Trygg, 2017; Short, Bocken, Barlow, & Chertow, 2014), also paying attention to ways firms do BM change (Brennan & Tennant, 2018; Franceschini & Pansera, 2015; Gauthier & Gilomen, 2016; Rajala, Westerlund, & Lampikoski, 2016) or on BMI and value proposition (Baldassarre, Calabretta, Bocken, & Jaskiewicz, 2017; Geissdoerfer, Bocken, & Hultink, 2016); others investigated BMI for sustainability transition (e.g., Battistella, Cagnina, Cicero, & Preghenella, 2018; Long, Looijen, & Blok, 2018; Schaltegger, Ludeke‐Freund, & Hansen, 2016; van Bommel, 2018). Also, the area of drivers for BMI is explored in some papers (Rantala, Ukko, Saunila, & Havukainen, 2018; Zollo, Cennamo, & Neumann, 2013), and a number of papers deal with BMI in the case of specific sectors, such as energy (Bolton & Hannon, 2016; Rossignoli & Lionzo, 2018), biogas (Karlsson, Hoveskog, Halila, & Mattsson, 2018), construction (Zhao, Chang, Hwang, & Deng, 2018), building (Leising, Quist, & Bocken, 2018; Zhao, Chang, et al, 2018; Zhao, Pan, & Chen, 2018) or other innovative firms (Karlsson, Halila, Mattsson, & Hoveskog, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors explored BMI for sustainability (Baumgartner & Rauter, 2017; Franca, Broman, Robert, Basile, & Trygg, 2017; Short, Bocken, Barlow, & Chertow, 2014), also paying attention to ways firms do BM change (Brennan & Tennant, 2018; Franceschini & Pansera, 2015; Gauthier & Gilomen, 2016; Rajala, Westerlund, & Lampikoski, 2016) or on BMI and value proposition (Baldassarre, Calabretta, Bocken, & Jaskiewicz, 2017; Geissdoerfer, Bocken, & Hultink, 2016); others investigated BMI for sustainability transition (e.g., Battistella, Cagnina, Cicero, & Preghenella, 2018; Long, Looijen, & Blok, 2018; Schaltegger, Ludeke‐Freund, & Hansen, 2016; van Bommel, 2018). Also, the area of drivers for BMI is explored in some papers (Rantala, Ukko, Saunila, & Havukainen, 2018; Zollo, Cennamo, & Neumann, 2013), and a number of papers deal with BMI in the case of specific sectors, such as energy (Bolton & Hannon, 2016; Rossignoli & Lionzo, 2018), biogas (Karlsson, Hoveskog, Halila, & Mattsson, 2018), construction (Zhao, Chang, Hwang, & Deng, 2018), building (Leising, Quist, & Bocken, 2018; Zhao, Chang, et al, 2018; Zhao, Pan, & Chen, 2018) or other innovative firms (Karlsson, Halila, Mattsson, & Hoveskog, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…SI between building owners and tenants have widely been discussed (e.g. Zhao et al , 2016; 2017), however, the SI among different stakeholders in the project delivery stage is less noticed. The results in the study revealed that conflict of interests between clients and PMs (SI5), PMs’ difficulty in understanding (SI1) and fulfilling the green requirements of clients (SI3) are three factors significantly influencing PMs’ job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Relative high cost premium is commonly considered as one of the top challenges in the deployment of green building (e.g. Hwang and Tan, 2012; Hwang et al , 2017; Zhao et al , 2017). WGBC (2013) reported that the cost premium for various types of green buildings falls within 0–12.5 per cent.…”
Section: Introductionmentioning
confidence: 99%
“…The selected 89 valid samples have more than 10 years of experience in residential development and more than 3 years of experience in GRBD. The questionnaire used a 5-point Likert scale, showing that the degree of preliminary factors ranged from "very unimportant" (1) to "very important" (5) [76][77][78].…”
Section: Introductionmentioning
confidence: 99%
“…In order to test the internal consistency among factors under each category, we used the Cronbach's alpha scale. When the value of Cronbach's alpha is 0.7 or higher, it normally indicates a reliable group classification set [77]. The Cronbach's alpha scores of the 3 elements and 18 categories were calculated (Shown in Table 1).…”
Section: Introductionmentioning
confidence: 99%